Ground Fault Location of Large Generator and External Components - Siteng ZHAO; Lin GUI; Qixue ZHANG; Xiangheng WANG (Zhongguo dianli)
A fault location method is proposed to distinguish the ground faults of large generators and their external components. It divides the generator and its external components into four regions: the generator, the high-voltage winding of excitation transformer, the high voltage winding of unit auxiliary transformer, and the remaining external components. According to the zero-sequence direction discrimination principle, the exclusion method is used to check and determine the location of the fault. The key to this location method is to measure the zero-sequence current of generator terminal and high-voltage side of excitation transformer/unit auxiliary transformer. It’s necessary to select the TA according to different regions where the fault occurs. The location method was verified by a series of real fault cases, which proved that the method can accurately locate the ground fault of the generator and its external components, with shortened troubleshooting time and in-time power recovery of the generator. The proposed fault location method has the value of popularization and application.